In vitro Evaluation of the Antimicrobial Effect of N-acetylcysteine and Photodynamic Therapy on Root Canals Infected with Enterococcus faecalis - Abu Hasna, Amjad; Khoury, Rayana Duarte; Toia, Cassia Cestari; GonÃ§alves, Glaucia Beatriz; de Andrade, Flaviana Bombarda; Carvalho, Claudio AntÃ³nio Talge; Camargo, Carlos Henrique Ribeiro; Valera, Marcia Carneiro (Iranian Endodontic Journal, 2020)
Introduction: This study aimed to evaluate the effectiveness of N-acetylcysteine (NAC), photodynamic therapy (PDT) and NAC with supplemental PDT in optimizing the removal of bacteria from infected dentinal tubules of root canals infected with Enterococcus (E.) faecalis biofilm. Methods and Materials: Eighty human teeth were randomly divided into 5 groups (n=16) according to the intracanal medication used: saline solution (control); calcium hydroxide (CH); NAC; PDT; NAC+PDT. Ten samples from each group were prepared for microbiological culture analysis (CFU/mL) and were inoculated with E. faecalis suspension for 21 days for biofilm development; the other six samples from each group were prepared for scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) and submitted to a 5-days contamination protocol including eight centrifugation cycles on every other day for dentinal tubules infection. For antimicrobial activity analysis by microbiological culture, the root canals were contaminated with E. faecalis biofilm, instrumented and then medicated according to the experimental groups. Three samples were collected from the root canals: after 21-days of contamination, immediately after the instrumentation and 14-days after the medication according to the experimental groups. The morphology of E. faecalis biofilm on the root canal walls and bacterial cells viability were assessed by means of SEM and CLSM, respectively. One-way ANOVA and Repeated Measures ANOVA tests were used to analyze the obtained data statistically. Results: CFU/mL analysis showed that CH, NAC and NAC+PDT promoted greater antibacterial activity with statistically significant difference compared to saline solution and PDT (P<0.0001). However, saline solution and PDT were statistically similar. Illustrative images by SEM confirmed partially the CFU/mL results. CLSM showed that all groups were effective eliminating E. faecalis except for the saline solution group. Conclusions: Based on this in vitro study NAC was bactericidal against E. faecalis biofilms regardless PDT stimulation, presenting similar antimicrobial activity to CH.